Astrocytic hamartoma in a case with tuberous sclerosis - Postaci, Sevinç Arzu; Turgut, Burak; Liman Uzun, Seda; Erdağ, Murat (Gazi Eye Foundation, 2019)
Tuberosclerosis is a multisystemic phakomatosis originating from embryonic ectoderm characterized by presence of hamartomatous tumours and central nervous system, skin, visceral organs and eye findings. The aim of this case report is detailed description of systemic and retinal findings of the disease with the help of investigations. The patient was a 4-year-old male under vigabatrin treatment and follow-up by neurology department of pediatrics for epileptic seizures. The patient was consulted to our outpatient clinic for control. Ophtalmologic examination showed visual acuities as 8/10 in both eyes. Chorioretinal depigmented areas were observed on the periphery of the fundus in both eyes . Fundus examination of the right eye showed an astrocytic hamartoma on the inferior temporal arch which was bulgy, hypopigmented, with the size of two optic discs and with no calcifications. Dilated venous vessels were observed on the proximal of this lesion. Also two astrocytic hamartomas with the size of half-disc were observed on the nasal of optic disc. OCT showed surface bulging on hamartomatous lesion, hyper-reflectance and disorganization on the inner retinal layers and shading on the outer retinal layers. In the management of tuberous sclerosis, genetic counseling and multidisciplinary follow up are necessary as the disease is multisystemic. © 2019 Gazi Eye Foundation. All rights reserved.
Keywords: Astrocytic hamartoma; Astrocytoma; Child; Retinal case; Tuberous sclerosis